A novel Learning Engagement Data Model (LEDM) for online attendance system - Aziman, Abdullah; Asar, Abdul Karim; Nur Alnisa’ Anis Alanna, Ruzelan (IOP Publishing, 2020)
Student engagement is a very interesting subject in higher education. While many studies assess student engagement through survey, this approach claimed in literatures is lack of contextual analysis for decision making. Our motivation in this study is to integrate a simple way to assess student engagement of face-to-face session in blended learning approach within the online attendance system by identifying the data model supporting insightful analytics. This study aims to propose a new learning engagement data model incorporating behaviour, emotional and cognitive engagement for online attendance system. We found an interesting insight which there is a relationship of student engagements with the learning outcomes attainment. Initial findings in this study show potential values how our proposal may benefit higher education in adopting smarter way to measure student engagement while taking student attendance during face-to-face session in blended learning implementation.